Can the control of invasive species be left to chance?. Issue 1 (2nd January 2016) - Quansah, Emmanuel; Parshad, Rana D.; Mondal, Sumona; Upadhyay, Ranjit Kumar
Abstract: Invasive species are said to be a bigger threat to native biodiversity than pollution, harvest, and disease combined. In order to preserve native flora, fauna, and natural resources of regions, the effective control of invasive species is imperative. We consider a three-species predator–prey model, where the top predator, functions as an invasive species, with the ability to grow explosively to 'uncontrollable' levels in a finite time, if unchecked. We investigate the effect of random environmental forces, on such explosive growth. We find that environmental noise alone, cannot prevent explosive growth in invasive populations. We interpret these results as showing that invasive species can strongly adapt to a randomly changing environment. We provide supporting evidence of such phenomenon, from the ecological literature. Our results are applicable to a wide variety of natural resource management practices.